A review of evolutionary algorithms for multi objective multi product multi modal distribution problem with a possible new approach. (1st January 2011) - Parthiban, P.; Venkateswara Reddy, P.; Arunachalam, S.
Transportation industry is a fairly large industry in today's globalised world, and has significant effect too. Each and every big or small industry is bound to use the transportation facilities or logistics. The main problems in this logistics operation are optimising the cost, time, distance travelled, back orders and surpluses. In most of the studies, one or two of the aspects mentioned above has been taken into consideration and solved accordingly. Again in a lot of studies, it was assumed that the demand structure, inventory structure, structure of cluster formation and structure of route formation are of deterministic nature. This study is reviewing the previous attempts to solve different aspects of distribution problems, and simultaneously proposing alternative way of attempts.